The aim of this research was to gain the profile of blood gasses of green turtle (Chelonia mydas) hatch. Blood gas of the green turtle was analysed after exposuring them at 28 oC and 50% of humidity for 24 hours in a pvc tube and at 34 oC under sunlight exposured with 47% of humidity for 30 minutes. The result showed the different values of blood gas contents. This result showed indication of metabolism activities and poikilothermic adaptation of green turtle hatch. This information can be used - RINI PUSPITANINGRUM; SEPTELIA INAWATI WANANDI; RONDANG ROEMIATI SOEGIANTO; MOHAMAD SADIKIN (HAYATI Journal of Biosciences, 2011)
The aim of this research was to gain the profile of blood gasses of green turtle (Chelonia mydas) hatch. Blood gas of the green turtle was analysed after exposuring them at 28 oC and 50% of humidity  for 24 hours in a pvc tube and at 34 oC under sunlight exposured with 47% of humidity for 30 minutes. The result showed the different values of blood gas contents. This result showed indication of metabolism activities and poikilothermic adaptation of green turtle hatch. This information can be used to support for turtle hatchery in Indonesia.